Behavioral Intentions of Bystanders to Image-Based Sexual Abuse: A Preliminary Focus Group Study with a University Student Sample. Issue 3 (3rd April 2023) - Mainwaring, Chelsea; Scott, Adrian J; Gabbert, Fiona
ABSTRACT: Image-based sexual abuse (IBSA) represents a form of technology-facilitated sexual abuse that encompasses the taking, creating, and/or sharing (including threats to share) of nude or sexual images without consent. Unlike physical sexual violence contexts, little is known regarding if and how bystanders intervene in IBSA contexts. The current preliminary study aimed to address this gap in the literature. Specifically, seven focus groups with a sample of 35 university students (31 females, 4 males) were conducted to explore how they think they would behave (i.e., their behavioral intentions) if they were bystanders to three different IBSA scenarios: non-consensual taking, non-consensual sharing, and threatening to share nude or sexual images. Transcripts were analyzed using thematic analysis and the following themes were identified: perpetrator-centered action, victim-centered action, justice-centered action, and intervention as a well-informed and controlled process . Participants discussed how they would intervene by approaching the perpetrator, either in a confrontational or non-confrontational way, or approach the victim to inform them of what was happening, provide advice, or to support them. They also discussed involving the police. However, some group members were against these forms of intervention, particularly approaching the perpetrator and involving the police. Finally, many participants indicated that their actions need to be well-informed. These findings highlight a wide range of bystander actions in IBSA contexts that have implications for the development of policies, educational materials, and measures of bystander intervention behavior in future research.